Failure is not an option: Entrepreneurship and the existential crisis of internationalization in the U.S. (3rd May 2022) - Glass, Chris R.; Cruz, Natalie I.
Abstract: Internationalization has become intertwined with efforts for institutions to compensate for declines in public funding with the development of new revenue streams. The purpose of this study is to understand the social construction of entrepreneurship in internationalization in the United States as well as explore the multiple meanings of entrepreneurship and its contradictions in discourse among senior international officers. The findings discuss and explore competing views, tensions and ethical complexities of the 'new entrepreneurism' increasingly common in internationalization, which blends creative problem‐solving with pressures for revenue generation. The findings of this study illustrate that as the world faces genuine existential crises that threaten the continued existence of our species on the planet, internationalization is in the midst of an identity crisis. The drift towards privatization is proving to be increasingly unsustainable and an entirely insufficient response to the existential threats that face the world.